2023
DOI: 10.3390/diagnostics13020322
|View full text |Cite
|
Sign up to set email alerts
|

Could Spinal Epidural Lipomatosis Be the Hallmark of Metabolic Syndrome on the Spine? A Literature Review with Emphasis on Etiology

Abstract: Spinal epidural lipomatosis is defined by an excessive amount of epidural fat in the spinal canal, usually in the lumbosacral tract: a well-known cause of lumbar pain and spinal stenosis with a possible wide range of neurological symptoms. Recent research data reveal that, nowadays, obesity has become the main cause of spinal epidural lipomatosis. Moreover, this condition was recently recognized as a previously unknown manifestation of metabolic syndrome. Radiological studies (CT and MRI) are the only tools th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 97 publications
0
2
0
Order By: Relevance
“…Including epidural lipomatosis among the main causes of stenosis with disc pathology and arthritis is an important and unique feature of this grading system. Recent literature has recognized that hypertrophy of epidural fat is one of the key elements in the development of symptoms and lumbar stenosis [50][51][52]. MRI is considered the most sensitive and comprehensive imaging tool available for the study of the lumbar spine, providing information in regard to all the structures involved in the pathogenesis of low back pain, including bone, disc, neural roots, facet joints, ligaments, paravertebral muscles, spinal canal, neural foramina, and epidural fat.…”
Section: Patient Preparation and Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Including epidural lipomatosis among the main causes of stenosis with disc pathology and arthritis is an important and unique feature of this grading system. Recent literature has recognized that hypertrophy of epidural fat is one of the key elements in the development of symptoms and lumbar stenosis [50][51][52]. MRI is considered the most sensitive and comprehensive imaging tool available for the study of the lumbar spine, providing information in regard to all the structures involved in the pathogenesis of low back pain, including bone, disc, neural roots, facet joints, ligaments, paravertebral muscles, spinal canal, neural foramina, and epidural fat.…”
Section: Patient Preparation and Managementmentioning
confidence: 99%
“…Including epidural lipomatosis among the main causes of stenosis with disc pathology and arthritis is an important and unique feature of this grading system. Recent literature has recognized that hypertrophy of epidural fat is one of the key elements in the development of symptoms and lumbar stenosis [ 50 , 51 , 52 ].…”
Section: Image-guided Minimally Invasive Treatmentsmentioning
confidence: 99%
“…LEL is a rare disease in clinical practice; however, approximately 6% of symptomatic cases of lumbar spinal stenosis are associated with LEL ( 2 , 3 ). Clinical manifestations include nerve root and cauda equina compression injury symptoms, such as neurogenic claudication, loss of sensation, lower limb weakness, cauda equina syndrome, and so on ( 3 , 4 ). If symptoms are mild, conservative treatment should be administered.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have indicated that the diagnosis rate of LEF is only 8%, and it is easily missed or misdiagnosed in clinical practice, which may delay the optimal treatment time and affect a patient's quality of life ( 4 , 5 ). Research on the diagnosis and treatment of LEF has increased in recent years, and numerous effective treatment methods have been proposed ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among spinal factors are included fractures, tumors, infections, inflammatory diseases, intervertebral disc pathologies, spondyloarthritis, spondylolisthesis, facet arthropathies, sacroiliac joint disease, and spinal epidural lipomatosis. 4,5 All these causes can play a role singularly or in combination. Notably, in the elderly, the association of many causes is frequently found simultaneously.…”
mentioning
confidence: 99%